2018
DOI: 10.1504/ijmie.2018.088383
|View full text |Cite
|
Sign up to set email alerts
|

Lean start-up awareness and effect on entrepreneurial intentions among Malaysian youths

Abstract: In an attempt to develop greater interest in enterprise start-up, this study examines the level of awareness of lean start-up model and its effect on entrepreneurial intentions among Malaysian youths. In this study, we argue that greater entrepreneurial interest could be ignited in the youths if lean start-up model is applied in teaching and learning. Using a survey, data were collected from 191 university students at three universities in Malaysia peninsula. These data were analysed with descriptive statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Finally, regarding the impact of emerging methodologies on entrepreneurship and innovation, Bieraugel (2015) stated that the use of LS can contribute to the reduction of uncertainties and fears about innovation, and Tolfo et al (2018) showed that industry practitioners and scholars have positive perceptions to AM enhancing entrepreneurial skills. The studies of Ladd and Kendall (2017) and Ekpe et al (2017) reported increased entrepreneurial intention to start new business and self-confidence in the ability to search for an idea in individuals exposed to LS. Bessant et al (2002) revealed that AM strengthen internal capabilities of organizations concerning the ability to change rapidly and continuously, while Trimi and Berbegal-Mirabent (2012) stated that the logic behind rapid iterations drives innovation and fosters product generation in a shorter period, wherein the value of such methodologies lies.…”
Section: Thematic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, regarding the impact of emerging methodologies on entrepreneurship and innovation, Bieraugel (2015) stated that the use of LS can contribute to the reduction of uncertainties and fears about innovation, and Tolfo et al (2018) showed that industry practitioners and scholars have positive perceptions to AM enhancing entrepreneurial skills. The studies of Ladd and Kendall (2017) and Ekpe et al (2017) reported increased entrepreneurial intention to start new business and self-confidence in the ability to search for an idea in individuals exposed to LS. Bessant et al (2002) revealed that AM strengthen internal capabilities of organizations concerning the ability to change rapidly and continuously, while Trimi and Berbegal-Mirabent (2012) stated that the logic behind rapid iterations drives innovation and fosters product generation in a shorter period, wherein the value of such methodologies lies.…”
Section: Thematic Analysismentioning
confidence: 99%
“…In addition to Europe, a number of papers report research conducted in other locations, with a small representation of Brazil (Melegati et al , 2019; de Paula and Araujo, 2016; Tolfo et al , 2018; Ximenes et al , 2015), the USA (Kumar et al , 2018; May, 2012), China (Li et al , 2014; Yang et al , 2019), Indonesia (Nirwan and Dhewanto, 2015), Singapore (Chan et al , 2019) and Malaysia (Ekpe et al , 2017). The small number of investigations outside Europe highlights the lack of research and opportunities in other continents, especially in developing countries.…”
Section: Descriptive Analysismentioning
confidence: 99%